2021
DOI: 10.7717/peerj.12315
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between HSPA4 and prognosis and immune regulation in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is an inflammation-associated tumor involved in immune tolerance and evasion in the immune microenvironment. Heat shock proteins (HSPs) are involved in the occurrence, progression, and immune regulation of tumors. Therefore, HSPs have been considered potential therapeutic targets. Here, we aimed to elucidate the value of HSP family A (Hsp70) member 4 (HSPA4) in the diagnosis and predicting prognosis of HCC, and its relationship with immune cell infiltration, immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Jiang et al found that cell-cycle activity was associated with antitumor immunity in ten TCGA cancer cohorts, including HCC, and identified that the expression of many cell-cycle pathway genes was positively correlated with antitumor immunity [ 40 ]. The efficacy of immunotherapy requires sufficient immune infiltration into the tumor microenvironment and depends on the expression of immune checkpoint molecules [ 41 , 42 ]. Recent studies have reported that CDKN2A is closely associated with immune infiltration of HCC [ 12 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al found that cell-cycle activity was associated with antitumor immunity in ten TCGA cancer cohorts, including HCC, and identified that the expression of many cell-cycle pathway genes was positively correlated with antitumor immunity [ 40 ]. The efficacy of immunotherapy requires sufficient immune infiltration into the tumor microenvironment and depends on the expression of immune checkpoint molecules [ 41 , 42 ]. Recent studies have reported that CDKN2A is closely associated with immune infiltration of HCC [ 12 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that HSPA4 is significantly correlated with the prognosis and immune regulation of HCC. Therefore, HSPA4 might be a potential diagnostic and prognostic biomarker as well as a therapeutic target for HCC [ 20 ]. In previous studies, these genes, including both MAPK1 and HSPA4, were not reported to be related to NASH but other liver-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , Tan et al (2020 ) further demonstrated that the activation of RIP3/MLKL-dependent necroptosis could increase the therapeutic sensitivity to gefitinib in NSCLC patients. Heat-shock protein family A (Hsp70) member 4 (HSPA4) was involved in the functional stabilization of mutated or aberrantly expressed genes in multiple tumors ( Lv et al, 2012 ) and had been identified to have a significant correlation with immune regulation and prognosis of hepatocellular carcinoma ( Shang et al, 2021 ). Notably, as the sole protective NRG for LUAD, CYLD Lysine 63 Deubiquitinase (CYLD) had been considered as the tumor suppressor and further demonstrated to be regulated by miR-96-5p and LncRNA GMDS-AS1 to inhibit the development of LUAD via a cellular assay and mouse tumor models ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%